Understanding tourists’ reactions to overtourism: a netnographic analysis of online discourses - Lonardi Serena; D'Acunto David; Confente Ilenia; Raggiotto Francesco (2024)
This study explores tourists’ perceptions of overcrowding in a nature-based destination and the role of overtourism in shaping the sustainability-related experiences shared online. Drawing on the perceived destination adaptation and tourists’ psychological reaction behaviors (i.e. approach, avoidance, and tolerance) theoretical fundamentals, this study investigates the tourists’ online discourse related to the triple bottom lime dimensions of sustainability (i.e. environmental, socio-cultural and economic). The study adopts a novel qualitative methodological approach in the sustainable tourism landscape by running a netnographic analysis on a sample of 1027 TripAdvisor reviews. The main findings confirm the negative impacts of overtourism on the tourists’ experience, indicating the presence of other tourists at the attraction as one of the main reasons of online complaints. However, while results exhibit the presence of tourists’ avoidance reaction (i.e. the negative reaction to mass tourism), tourists did not show an approach reaction (i.e. positive feelings about crowding places) in their reviews. Instead, a compromise reaction was found among respondents, with some reporting great experiences even on busy attractions and others suggesting how to avoid the crowds. Results also exhibit how the paradoxes of sustainable tourism are not fully recognized by tourists, with reviewers complaining online about overtourism tending to never acknowledge to be part of the problem, and often suggesting their peers to visit the attraction on a less busy time, thus contributing to increased crowding. Destinations suffering of overcrowding are thus advised to actively monitor their reviews and respond to try mitigating the potential negative effects of peers suggestions.